Campo Verano Revisited - Delgado Orusco, Eduardo (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2014)
The recent burial of Javier Carvajal in the Spanish Pantheon in Rome which he designed with José María García de Paredes half of the fifties, becomes relevant a review to this small installation. Its project strategies contributed to seat the foundation of the modern architecture in Spain after the postwar decade, identified generally by an attempt to historicist recovery. The geographically peripheral location of the Roman Academy where the work is located, and the Italian context in general, helped the development of a strong experimental project which increases the interest of this research. This is one of the first works constructed by the authors but nevertheless it provides interpretive clues to their future works, whether them alone or as a team again.